Meaningful English learning: Integrating deep learning-CBL, and reflection e-portfolio in supporting local wisdom of Batang - Yan Imam Santoso; Prasetyawan Aji Sugiharto (Journal of English Language and Pedagogy, 2025)
This study aims to address the challenges of 21st-century English language learning by integrating Deep Learning and Case-Based Learning approaches and utilising Reflection E-Portfolios as an assessment tool. This phenomenological approach focuses on the experiences of 20 English teachers and 40 students. Data collection in this study utilised Focus Group Discussions, Interviews, Observations, and Questionnaires. Based on the analysis of the collected data, The research findings indicate that the implementation of Deep Learning and Case-Based Learning approaches can be effectively applied in subjects with local wisdom themes. This learning model demonstrates success in building students' contextual and meaningful learning experiences by enabling them to connect theoretical concepts with real classroom cases and analyse authentic problems more critically. On the other hand, the Reflection E-Portfolio shows evidence that this medium greatly facilitates students and teachers in evaluating their learning in the classroom. Therefore, it can be concluded that this learning model and assessment medium greatly support the development of students’ potential—particularly their critical thinking, problem-solving skills, collaboration, communication, creativity, metacognitive awareness, and cultural awareness. However, it cannot be avoided that facilities, time, and teachers' capabilities need to be honed and fully supported, both materially and non-materially, to achieve relevant, high-quality, meaningful learning that can develop students' skills.